Dampak Pemilihan Kepala Daerah Langsung dalam Pembinaan Aparatur Sipil Negara (Studi Kasus pada Pemerintah Provinsi Kalimantan Selatan): The Impact of Direct Election of Regional Heads in the Development of State Civil Apparatus (Case Study on the Government of South Kalimantan Province) - Suhardjo, Suhardjo (Anterior Jurnal, 2019)
Direct Regional Head Elections that occur in Indonesia are based on Law Number 1 of 2015 concerning the Establishment of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents, and Mayors Becoming Laws, which are in the legislation regulating the procedure for the election of Governors, Regents, and Mayors, as well as this, has occurred the South Kalimantan Province post-conflict local election held on 9 December 2015 to elect the Governor of South Kalimantan for the 2016-2021 period. In this study, researchers chose to use a qualitative descriptive approach. Data collection techniques by means of interviews and observation and documentation. The results of this study are The Impact of the Election of Direct Regional Heads in the Development of State Civil Apparatus Careers in the South Kalimantan Provincial Government in terms of State Civil Apparatus Social is the impression/perception for the State Civil Apparatus that the Regional Head is elected from the election directly as if there is always a connection with supporting the support of the State Civil Apparatus to candidates for Regional Head Candidates when they start the campaign process until the election. (b) Judging from the Economic aspects of the State Civil Apparatus, particularly the South Kalimantan Provincial Government, those in income as long as those originating from Salaries and allowances are relatively still in accordance with the provisions of the legislation concerning inherent Salary and Job Allowances, and the reference to Regional Allowances.